Internet and social media in Malaysia: Development, challenges and potentials - Wok, Saodah; Mohamed, Shafizan (Intech Open, 2017)
The penetration of the Internet and social media has helped Malaysia abreast with the other developed countries. Nonetheless, being a multicultural country, Malaysia has to ensure her multiracial population lives in harmony and peace. This happens with the help integrated the media control and regulations exercise in Malaysia: the Printing Presses and Publications Act, Film Censorship Act, Broadcasting Act, Communication and Multimedia Act, and media ownership control. Many researches have been conducted pertaining to the Internet and social media that have been published locally in line with the development of the Internet and the social media in Malaysia. Similarly, the new media is also subjected to its being controlled through methods such as controlling the Internet, blocking and filtering, and content removal. The paper also looks into the impact of the Internet and social media on its civil society, thus creating a momentum to promote toward giving suggestions for future research involving not only theories but also models using more sophisticated analyses. More research can be done and the future of research is bright. Other areas that can be looked at are the impacts of the Internet and social media on the young populace of the nation.